Study the effect of different temperatures in the growth and development of Been Beette Acanthoselides obtectus (Coleoptera: Bruchidae) - Sultan AL-qeraqouly, Ammar Ahmed; Abdulrazak Gebara, Abdulwahab (Iraqi Journal of Science, 2023)
This research includes a study of the effect of four temperatures (25, 30, 35, 40m◦) with relative humidity 65% on some biological aspects of the Bean beetle Acanthoselides obtectus on the Bean seeds under laboratory conditions. The results showed that the effect of different temperatures is clear on biological of Bean beetle. Differed period necessary for the growth and development of each stage of the insect in different temperatures . The results of statically analysis showed a significant difference in the life cycle when all temperatures except the period between temperature 35 and 40m◦ , respectively. Where the average of those period, 60.75, 35.5, 20.34 and 19.27 days and also different temperatures significant effects is clear in the growth of eggs reaching the average growth of eggs 11.3 , 6.40 , 4.17 and 2.99 days. Whereas the mean adult longevity recorded were 15.5 , 12.2 , 6.3 and 3 days for males , and 13.7 , 7.2 , 5.55 and 4.3 days for females at temperatures of 25 , 30 , 35 and 40 , respectively .